2010
DOI: 10.1055/s-0028-1100910
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiac complications after spine surgery

Abstract: Study design: Registry study using prospectively collected dataObjective: To determine risk factors for cardiac complications in spine surgery.Methods: The Spine End Results Registry 2003–2004 is an exhaustive database of 1,592 patients who underwent spine surgery at the University of Washington Medical Center or Harborview Medical Center. Detailed information regarding patient demographic, medical comorbidity, surgical invasiveness and adverse outcomes were prospectively recorded. The primary outcome of measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…7,16,18,19,24 The CCI was not specifically designed to assess patients undergoing spine surgery, and the usefulness of the CCI score to accurately predict complication occurrence after spine surgery remains uncertain. 2,22,44 The ACS NSQIP Surgical Risk Calculator was developed from a multi-institutional database of surgical procedures across all surgical specialties and draws on a model utilizing 21 preoperative factors to predict postoperative outcomes in individual patients. 3 The ACS NSQIP Surgical Risk Calculator has been shown to perform as well as procedure-specific risk calculators for colon surgery patients.…”
mentioning
confidence: 99%
“…7,16,18,19,24 The CCI was not specifically designed to assess patients undergoing spine surgery, and the usefulness of the CCI score to accurately predict complication occurrence after spine surgery remains uncertain. 2,22,44 The ACS NSQIP Surgical Risk Calculator was developed from a multi-institutional database of surgical procedures across all surgical specialties and draws on a model utilizing 21 preoperative factors to predict postoperative outcomes in individual patients. 3 The ACS NSQIP Surgical Risk Calculator has been shown to perform as well as procedure-specific risk calculators for colon surgery patients.…”
mentioning
confidence: 99%
“…Previous studies established several clinical and laboratory predictors of perioperative complications in patients undergoing spinal surgery. [4][5][6][7][8][9][10] However, none of these studies comprehensively evaluated preoperative nutritional status in these patients. Malnutrition was associated with an increased risk of PAEs such as perioperative infection, longer hospital stays, and worse outcome after surgery in a variety of patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that prolonged operative time, older age, obesity, and the presence of significant comorbidities are associated with a higher incidence of complications in spinal surgery, such as surgical site infection, delayed wound healing, and cardiovascular complications. [6][7][8][9] These studies showed that preoperative state of health is a key consideration when deciding whether or not it is safe to proceed with elective spine surgery, especially in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The occurrence of postoperative pulmonary complications significantly increased the in-hospital morbidity and mortality, as well as prolonged hospitalization, increased costs, and compromised quality of life. 12,[14][15][16][17] However, the risk factors of pulmonary complications after minimally invasive surgery for elderly patients with VCFs have not been reported and no risk assessment table established.…”
Section: Introductionmentioning
confidence: 99%